Study of Corona Configurations under DC Conditions and Recommendations for an Identification Test Plan. (June 2020) - Abdul Madhar, Saliha; Mráz, Petr; Rodrigo Mor, Armando; Ross, Robert
Highlights: Gives in-depth physical interpretation of the behavioral features of corona under DC. Plot of Qi+1 vs. Δti+1 is more robust to outliners in comparison to the PSA plots. Presence of intermittent corona and self-sustaining corona serve as useful pointers. DC configuration with needle on ground is identified as the riskiest amongst all. A unique test plan for the identification of the corona configuration is proposed. Abstract: Corona is one of the most common forms of partial discharge (PD) occurring in high voltage (HV) energy systems. The corona mechanism in air is not exclusive to the field of energy applications but has also been widely studied by physicists to theorize mechanisms of charge transfer during the different phases of gas discharge. The phases of the discharge and its corresponding behavior with alternating voltage (AC) are well established and represented through various discharge trends, patterns and stages. This not only makes the identification of the PD defect possible but also helps evaluate the risk. This paper investigates corona configurations under DC stress in an attempt to create a similar outline of the defect as exists under AC. The defect is studied in terms of the pulse sequence information. The measurement system requirements are kept within a realistic realm to preserve applicability to industrial measurements. Finally, it makes selective recommendations for the effective identification of the discharge condition under DC stress.